Combined Endoscopic Endonasal Transorbital Approach with Transconjunctival-Medial Orbitotomy for Excisional Biopsy of the Optic Nerve: Technical Note - Koutourousiou, Maria; Gardner, Paul A.; Stefko, S. Tonya; Paluzzi, Alessandro; Fernandez-Miranda, Juan C.; Snyderman, Carl H.; Maroon, Joseph C. (Journal of Neurological Surgery Reports, 2012)
Background Access to the intraorbital optic nerve segment can be facilitated via a transcranial approach that allows access to the entire orbital cavity. The endoscopic endonasal approach (EEA) combined with a transconjunctival-medial orbitotomy represents an alternative technique to achieve the same goal.Objective Report a surgical technique that allows total resection of the intraorbital optic nerve with minimal trauma and excellent results. Further extend and define the limits and indications of the EEA to orbital surgery.Methods A patient with rapidly progressive, but asymmetric, vision loss underwent EEA for optic nerve biopsy. Due to the undetermined histopathological diagnosis and complete unilateral vision loss, diagnostic total optic nerve resection was indicated. The entire intraorbital length of the nerve was resected via an endoscopic endonasal transorbital approach combined with transconjunctival-medial orbitotomy.Results A 2-cm intraorbital nerve segment was sent for pathological examination. The patient maintained normal extraocular movements and experienced no complications. The postoperative course was uneventful and the patient was discharged the next day.Conclusion The EEA provides another option for access to the entire optic nerve. It is a safe and effective technique lacking cosmetic defects and providing an alternative corridor to traditional transcranial approaches to the orbit.
Keywords: endoscopic endonasal approach; optic nerve resection; orbital surgery; transconjunctival-medial orbitotomy